Electro mechanical properties changes of LDPE doped with industrial type MgO for cable insulation purposes - Sherif Haggag; Loai Nasrat; Hanafy Ismail (Institute of Advanced Engineering and Science, 2021)
This manuscript introduces the changes of a comprehensive electromechanical properties bundle for low density polyethylene compounded to microscale magnesia (LDPE/MgO) to obtain electrical cables insulating material. Composites of various filler loading weight ratios were prepared by melt intercalation technique; multiple samples were produced in sets as they were cut with definite dimensions as per recommendations of the related testing standard then electrically and mechanically examined following the instruction dictated by the code while preserving typical test condition for all sets. Dielectric strength, volume resistivity, capacitance, and loss angle were the tests of the electrical test pack, while elongation, tensile strength, and melt flow rate were the mechanical and rheological tests applied. Test’s findings were compared to each other’s and to the base material to identify the differentiation. Electrical test results show improvements in the composite features at low loading percentages, whereas the mechanical tests revealed a deterioration in the mechanical properties along with all ratios under investigation. The research aims to determine the compositing benefit extents and drawbacks when a conventional compounding method and inexpensive filler are used, incurring marginal cost impact.